Dragers van het vangnet. De publieke rol van Nederlandse sociale diensten (1980-1998) - Rodenburg, Hans (TSEG - The Low Countries Journal of Social and Economic History, 2019)
This article examines the public role of Dutch social service organizations during the 1980s and 1990s, amidst the so-called ‘crisis of the welfare state’. The story focuses on the association for directors of social service organizations, DIVOSA, which emphatically presented itself as a representative of all people living on a minimum income. As the association was formed by public officials, this representative role caused a fundamental tension with the task of implementing governmental policies aimed at cutting welfare state expenses and activating recipients. Based on extensive research in the archives of DIVOSA, this article adds to our understanding of the socioeconomic history of the Dutch welfare state.